The Effect of Health Education on Pregnancy Danger Signs on Increasing Knowledge of Third Trimester Pregnant Women - Chendany, Thasha Chindy; Kristiana, Dita (International Journal of Health Science and Technology, 2023)
The success of maternal health programs can be measured using the main indicator of Maternal Mortality Rate (MMR). One of the factors causing high MMR is the lack of knowledge of III trimester pregnant women about the danger signs of pregnancy. Providing health education to pregnant women is one way to increase knowledge so that third trimester pregnant women can make decisions quickly when facing dangerous signs of pregnancy. One that affects knowledge is education. The educational process is expected to bring changes in knowledge, attitudes and skills. The purpose of this study was to determine the effect of health education about the danger signs of pregnancy on increasing the knowledge of III trimester pregnant women. This research method uses  pre-experimental design with one-group pre-test post-test design. Data collection method with primary data using questionnaires. The population of this study amounted to 42 III trimester pregnant women, the sample in this study was 38 III trimester pregnant women using purposive sampling and Wilcoxon test. The results of this study show an increase in knowledge of III trimester pregnant women as evidenced by the results obtained  a p-value of 0.000 where the p-value  is <0.05.  This means that health education about the danger signs of pregnancy is effective in increasing the knowledge of third trimester pregnant women at PMB Ummi Latifah Bantul.